A Class of Transformation Matrices and Its Applications - Wenhui Liu; Feiqi Deng; Jiarong Liang; Haijun Liu (Abstract and Applied Analysis)
This paper studies a class of transformation matrices and its applications. Firstly, we introduce a class of transformation matrices between two different vector operators and give some important properties of it. Secondly, we consider its two applications. The first one is to improve Qian Jiling's formula. And the second one is to deal with the observability of discrete-time stochastic linear systems with Markovian jump and multiplicative noises. A new necessary and sufficient condition for the weak observability will be given in the second application.